Diagnosis and Management of Cystic Fibrosis Exacerbations - Milinic, Tijana; McElvaney, Oliver J.; Goss, Christopher H. (Seminars in Respiratory and Critical Care Medicine, 2023)
With the improving survival of cystic fibrosis (CF) patients and the advent of highly effective cystic fibrosis transmembrane conductance regulator (CFTR) therapy, the clinical spectrum of this complex multisystem disease continues to evolve. One of the most important clinical events for patients with CF in the course of this disease is acute pulmonary exacerbation (PEx). Clinical and microbial epidemiology studies of CF PEx continue to provide important insight into the disease course, prognosis, and complications. This work has now led to several large-scale clinical trials designed to clarify the treatment paradigm for CF PEx. The primary goal of this review is to provide a summary and update of the pathophysiology, clinical and microbial epidemiology, outcome and treatment of CF PEx, biomarkers for exacerbation, and the impact of highly effective modulator therapy on these events moving forward.
Keywords: FEV1; respiratory symptoms; pulmonary exacerbations; cystic fibrosis; treatment duration